THE COMPOSITION OF SOLID SOLUTIONS CRYSTALLISING FROM AQUEOUS SOLUTIONS: THE INFLUENCE OF SUPERSATURATION AND GROWTH MECHANISMS - Pina C.M.; Enders M.; Putnis A. (My University, 2000)
In this paper we present a new approach to the problem of the crystallisation in solid solution-aqueous solution (SS-AS) systems, in which two main controlling factors have been considered: (i) the supersaturation state of the multicomponent solution in contact with the growing crystal and (ii) the growth mechanisms, operating at a molecular scale on the various faces of the crystal. Supersaturation has been evaluated as a function of the solid solution (the β function) and the transitional supersaturation between spiral growth and two dimensional nucleation mechanisms has been considered as a linear function of the solid composition (the β* line). By superimposing β functions and β* line on a supersaturation-solid composition diagram, we can define compositional regions growing according to different growth mechanisms. In order to test our model, a number of in situ Atomic Force Microscope (AFM) experiments have been conducted in the Ba2+-Sr2+-SO42--H2O system, using barite (001) as the substrate. The general growth behaviour observed is consistent with the predictions given for a number of initial aqueous solution compositions. Microprobe analysis shows that the new (001) layers grown under conditions where the maximum supersaturation corresponded to intermediate compositions of the (Ba,Sr)SO4 solid are very Sr-rich. A qualitative explanation for such a compositional shift is given on the basis of nucleation rate calculations in the Ba2+-Sr2+-SO42--H2O system. Finally we discuss the effect of the substrate on the formation and distribution of two-dimensional (Ba,Sr)SO4 nuclei on a barite (001) surface.
Keywords: SUPERSATURATION; GROWTH MECHANISMS; SOLID SOLUTION; BARITE; ATOMIC FORCE MICROSOCOPY